Goethite-Bound Phosphorus in an Acidic Subsoil Is Not Available to Beech (Fagus sylvatica L.) - Klotzbücher, Anika; Schunck, Florian; Klotzbücher, Thimo; Kaiser, Klaus; Glaser, Bruno; Spohn, Marie; Widdig, Meike; Mikutta, Robert (Frontiers in Forests and Global Change, 2020)
In forests, where supply of bioavailable P from easily weatherable primary minerals is small, plants are thought to recycle P efficiently by uptake of P released from decomposing forest floor material. Yet, a share of the P is leached into subsoil where it is strongly adsorbed onto reactive surfaces of pedogenic Fe and Al oxides. This raised the question whether P leached into subsoil is also recycled. In order to investigate the mobilization of P bound to hydrous Fe oxides, we conducted a mesocosm experiment in a greenhouse. Beech saplings were grown for 14 months in subsoil material (Bw horizon from the P-poor Lüss forest) with added goethite-P adsorption complexes, either in inorganic (orthophosphate) or in organic (phytate) form. Four types of control mesocosms were run: soil only and soil mixed with either dissolved orthophosphate or dissolved phytate or goethite. At the end of the experiment, neither total P mass in trees nor P contents in leaves differed between the treatments. According to leaf nutrient contents, plant growth was strongly limited by P in all treatments. Yet, total P mass in trees did not increase over the course of the experiment. Thus, despite of its P demand, beech was not able to acquire P from goethite surfaces within two vegetation periods. Also P added in dissolved form to the soil as well as native soil P were not available. This suggests that once inorganic and organic P is bound to pedogenic metal oxides in mineral soil, it is not recycled, which can be an explanation for field data demonstrating quantitatively significant stocks of P in subsoil of P deficient forests.